PENGARUH CORPORATE GOVERNANCE DAN KARAKTERISTIK PERUSAHAAN TERHADAP KETEPATAN WAKTU PELAPORAN PERUSAHAAN DI INTERNET (CORPORATE INTERNET REPORTING TIMELINESS) - RUSDIANTI, RANI (Jurnal Akuntansi AKUNESA, 2014)
This study examinesmanagerialownership, blockholderownership,public ownership, the proportion ofindependent board, firm size, profitabilityandliquidityon thetimeliness ofcorporate internet reporting. Samples fromthis studyarecompanieslisted onthe Indonesia Stock Exchangein 2013aftereligiblepurposivesamplingso thatamounts to42 companies. The data analysis techniqueusedin this studyishypothesis testingwithmultiple linear regression method. The results showedthat thevariablesof managerialownership, blockholderownership, profitabilityandliquiditydoes noteffect ontimeliness ofcorporate internet reporting. Whilepublic ownershipvariables, the proportionof independent boardand firm sizeeffect ontimeliness ofcorporate internet reporting.In addition, the sevenvariablessimultaneouslyeffect ontimeliness ofcorporate reportingon the Internet.   Keywords: timeliness, corporate internet reporting, corporate governance, firm characteristics.